2019
DOI: 10.1002/jia2.25418
|View full text |Cite
|
Sign up to set email alerts
|

Two‐drug antiretroviral regimens: an assessment of virologic response and durability among treatment‐experienced persons living with HIV in the OPERA® Observational Database

Abstract: Introduction Two‐drug regimens (2‐DR) have the potential to be a viable solution to the challenges of treatment complexity, cost, adverse effects and contraindications. We sought to describe the real‐world use and effectiveness of 2‐DR among persons living with HIV (PLHIV) in the United States. Methods We analysed data for 10,190 treatment‐experienced patients from the OPERA® Observational Database initiating a new 2‐DR or three‐drug regimen (3‐DR) between 1 January 2010 and 30 June 2016. Multivariate Cox Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…The authors also proposed clinical reassessment schedules for at-risk patients, de ned as those who are older than 50 years, have 2 or more comorbidities or receiving polypharmacy (generally considered as 6 or more medications). Another international study also indicated that multi-comorbidities were higher in the 2-ART cohort compared with 3-ART cohort [21]. The authors also found that patients initiation 2-ART were older, had similar regimens compared to our study, and had shorter time-to-discontinuation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The authors also proposed clinical reassessment schedules for at-risk patients, de ned as those who are older than 50 years, have 2 or more comorbidities or receiving polypharmacy (generally considered as 6 or more medications). Another international study also indicated that multi-comorbidities were higher in the 2-ART cohort compared with 3-ART cohort [21]. The authors also found that patients initiation 2-ART were older, had similar regimens compared to our study, and had shorter time-to-discontinuation.…”
Section: Discussionsupporting
confidence: 75%
“…The authors also found that patients initiation 2-ART were older, had similar regimens compared to our study, and had shorter time-to-discontinuation. [21] Although we did not test any causality, it seems logical that patients who are older, have more co-morbidities, and take more co-medications will likely need a treatment strategy to reduce drug-drug interaction (DDI) or drug adverse events. A 2-ART can be one option for these patients.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, we included a relevant number of subjects treated with lastgeneration InSTI-based 2DR (i.e. dolutegravir + lamivudine or rilpivirine), who were poorly represented in previous studies exploring 2DRs, where PI-based 2DRs were predominant [34,35]. The combinations of dolutegravir + lamivudine or rilpivirine have demonstrated high efficacy in clinical trials [20][21][22], are characterized by better tolerability than PI-based 2DRs and are available in single tablet formulations; these characteristics make them more suitable for wide use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preliminary findings did not demonstrate a detrimental effect of 2DRs on virological control in reservoirs and on inflammatory profile [7,[29][30][31][32]. However, very few studies comparing 2DRs and 3DRs in a real-life setting are available [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ART regimens with two ARVs (3TC plus DTG or darunavir/ritonavir (DRV/r), DTG plus rilpivirine (RPV), or DTG plus DRV/r) have been introduced into clinical practice following studies that have shown them to be effective in achieving virologic suppression in treatment-naive adults [ 90 , 96 , 97 ] and/or maintaining virologic suppression in treatment-experienced adults [ 98 103 ], with no evidence of the emergence of HIVDR mutations to either of the ARVs used. Studies have shown that dual ART regimens are non-inferior to standard triple ARV regimens, and provide the opportunity to reduce adverse effects of ARVs and simplify ART regimens [ 90 , 97 100 , 104 , 105 ]. Currently recommended dual ART regimens are either INSTI-based, PI-based, or a combination of an INSTI with a boosted PI [ 63 , 106 ].…”
Section: Evolution Of Hiv Drug Resistancementioning
confidence: 99%